Relationship between logical reasoning and academic achivement among secondry school students - Hassan, Aminuddin; Ahmad, Nor Aniza; Mohd Noor, Nur Fadzlillah Amira (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Learning in Malaysian context emphasizes the acquisition of scientific skill, thinking skills and the inculcation of scientific attitudes and noble values. Besides that the acquisition of scientific and technological knowledge and its application to the natural phenomena and students experience in daily life are also equally emphasized. The purpose of this study was to gauge the acquisition of logical reasoning abilities which is including conservational reasoning, proportional reasoning, controlling variables, combinatorial reasoning, probabilistic reasoning and correlational reasoning among Form 4 students in their academic achievement. This study was also aimed to ascertain if there is any significant difference in student’s acquisition of logical reasoning abilities based on student’s gender and academic achievement. This was a non-experimental quantitative research and sample survey method was used to collect data. In this study, samples were selected by using a cluster random sampling technique. Independent sample t-test and one-way ANOVA were used to test the stated null hypothesis at a predetermined significance level, a = .05. Research findings shows that the rural secondary school student’s acquisition of logical reasoning abilities was low. The average item mean for all the subscales, except conservational reasoning, were lower than the overall average item mean. This research also revealed that up to 96 per cent of the respondents were categorized at the concrete operational stage meanwhile only 4 per cent were categorized at the transitional stage. This study also found that there is no significance difference in the mean of logical reasoning abilities, except conservational reasoning based on student’s gender, but there is significance differences based on student’s academic achievement for the secondary school students were found. These research findings revealed some meaningful implications to those who are involved directly or indirectly in the development.